2005
DOI: 10.1089/neu.2005.22.680
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Behavioral Characterization of a Novel Cervical Spinal Cord Displacement Contusion Injury in the Rat

Abstract: Cervical contusive trauma accounts for the majority, of human spinal cord injury (SCI), yet experimental use of cervical contusion injury models has been limited. Considering that (1) the different ways of injuring the spinal cord (compression, contusion, and transection) induce very different processes of tissue damage and (2) the architecture of the spinal cord is not uniform, it is important to use a model that is more clinically applicable to human SCI. Therefore, in the current study we have developed a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 66 publications
7
103
1
3
Order By: Relevance
“…Behavior was not assessed in the present study. However, it has been reported that rats with contusive SCI at their C5 segment improved to weight-supported locomotion in the open field between the first and second week post-SCI (Pearse et al, 2005). Rats with contusive SCI at their C4-5 segments also were unable to perform a pellet retrieval task until at least 3 weeks afterward due to a lack of limb elevation, shoulder extension, and elbow extension (Schrimsher and Reier, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Behavior was not assessed in the present study. However, it has been reported that rats with contusive SCI at their C5 segment improved to weight-supported locomotion in the open field between the first and second week post-SCI (Pearse et al, 2005). Rats with contusive SCI at their C4-5 segments also were unable to perform a pellet retrieval task until at least 3 weeks afterward due to a lack of limb elevation, shoulder extension, and elbow extension (Schrimsher and Reier, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…3 As with the MASCIS and IH devices, the OSU impactor has recently been used to induce injury in the cervical spine of the rat. 15 A limitation of the device is that it is sometimes challenging to determine the zero distance for the impactor as the spinal cord and cerebrospinal fluid is displaced slightly when initially loaded.…”
Section: Infinite Horizon (Ih) Impactormentioning
confidence: 99%
“…Verify the injury visually by bruising on the spinal cord ( Figure. 5E, arrow) and check the injury parameters provided by the NYU software 12,17 ( Figure 6). 7.…”
Section: Stabilizing the Vertebrae And Performing The Impact Injurymentioning
confidence: 99%
“…Positional shifting of the target spine during contact between the impact plunger and the spinal cord alters the resultant injury force. The cervical contusive SCI model is a more clinically relevant model than other forms of SCI, as approximately 50% of human SCI cases occur at this level 8 , and several SCI studies have been performed using animal cervical injury models [9][10][11][12][13][14] . Although contusive SCI models often utilize some form of stabilization by clamping the spinal processes anterior and posterior to the injury site, this preparation is difficult for producing cervical SCI.…”
Section: Introductionmentioning
confidence: 99%